HOTSEP Analysis to Develop Disaster Research Integrated Book for Vocational Education (Drica) in 21st-Century - Primarini, Hendrica Etmi; Rahmayanti, Henita; Widiasanti, Irika; Ichsan, Ilmi Zajuli; Koc, Isil; Rogayan Jr., Danilo V.; Darussyamsu, Rahmawati; Titin, Titin; Marhento, Giry; Nurfadhilah, Nurfadhilah; Sa’diyah, Rika (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This study analyzed Higher-Order Thinking Skills of Environmental Problem (HOTSEP). It was conducted in March 2021. The sample comprised 114 vocational high school students, 66 male and 49 female students from several schools in Jakarta, Indonesia. The data was collected online using Google Form and Microsoft Excel for data analysis. The results showed that the HOTS score with analyzing environmental problems (C4) obtained an average score of 50. The thinking aspect of evaluating environmental problems (C5) obtained an average score of 49. The thinking aspect of making programs to overcome environmental problems (C6) obtained an average score of 47. Therefore, the study showed that the HOTS scores were relatively low since the average score was 51. The results showed that the HOTSEP score on the criticizing environmental problems (C4) obtained an average score of 24. The thinking aspect of environmental problem solving (C5) obtained an average score of 25. Furthermore, the thinking aspect of environmental innovation development (C6) obtained an average score of 23. Therefore, the study showed that the HOTSEP score was poor since the average score was 26. The research results suggest that learning media employed requires an improvement related to disaster mitigation. One media that can be developed is Disaster Research integrated book for Vocational Education (Drica). It can be concluded that the research results generally indicate that the vocational education students remain lacking in the HOTSEP aspect.